ACUTE TOXICITY OF MERCURY CHLORIDE TO TRICHOPTERA LARVAE - Hasriyanty - Hasriyanty; Alam Anshary; Shahabuddin Saleh; Moh. Yunus (AGROLAND The Agricultural Sciences Journal (e-Journal), 2020)
Mercury waste from gold mining activities that contaminate the environment is very harmful to the living organisms including aquatic insects. This study aims to analyze the acute toxicity of mercury on Trichoptera larvae that commonly used as a bioindicator of water quality.The study was arranged in a completely randomized design with six-levels of mercury chloride (HgCl2) concentrations, namely: 0.00; 0.001; 0.005; 0.1; 0.2; and 0.3 mg / l HgCl2. A total of 20 insects larvae were used for each concentration and the insect mortality was observed in four times (30, 60, 90, and 120 minutes). The results showed that the mortality of Trichoptera larvae had occurred at 30 minutes after observation. The LC-50 value of mercury chloride against Trichoptera was 0.048 ppm. Larval mortality increased with the increase of the mercury concentration and the exposure time. These results indicate the acute toxicity of mercury chloride to Trichoptera larvae. The effect of mercury on morphological changes of the Trichoptera larvae is also observed and discussed.